Analisis Faktor Keterlambatan Pemasangan Meter Baru Menggunakan Metode Decision Tree Pada PT PLN Unit Layanan Pelanggan Daerah Pringgabaya Lombok Timur - Yahya, Yahya; Sandi, Arnila (Jurnal PRINTER: Jurnal Pengembangan Rekayasa Informatika dan Komputer, 2025)
PT. PLN (Persero) ULP Pringgabaya is one of the units established by PT PLN to be able to provide direct services to the community in areas with smaller coverage. However, the use of electricity by the community has increased the demand for the installation of new meters. This study aims to analyze the causes of delays in the installation of new meters. In order to classify the highest causes of installation delays, the Decision Tree method is used. The number of data sets used is 700 data with attributes, such as the distance of the location to the PLN network (Meter), electric voltage (Volt), customer contact, SLO (Certificate of Operational Worthiness), Installation and Installation Status. From the calculation results, the acquisition includes Distance <= 37 M from the PLN network, voltage >= 220 Volts, inactive contacts, old SLOs issued, and uninstalled installations. Testing was carried out 10 times using cross validation with 100% accuracy results with an AUC value of 1.00, which means that the use of the decision tree algorithm can be utilized in determining the classification of the causes of delays in the installation of new meters at PT PLN ULP (Customer Service Unit) Pringgabaya. So it can be concluded that the cause of the delay in the installation of new meters at PT PLN ULP (Customer Service Unit) Pringgabaya is not caused by service criteria but is influenced by distance, voltage, and new customer contacts.